Medical Spanish - Whitney Ann Cesari; William F. Brescia; Kabir Harricharan Singh; Adeleke Oni; Anureet Cheema; Catherine Coffman; Aaron Creek; Crisanto Torres; Marissa Mencio; Stacy Clayton; Carmen Weaver; Joey Weaver (Association of American Medical Colleges, 2012)
Abstract In this web-based module, medical students work through lessons that will help them to communicate conversationally with Spanish-speaking patients in a clinical setting. It contains ten individual lessons on topics that include "Getting Started with Medical Spanish," "Cardiovascular Pulmonary Exam," "Treating the Patient," OB/GYN Exam," and others. The results of the pre- and posttest were compared to determine if the course was effective. The students took an attitude survey at the end of the course so that we could assess their impression of the course. Based on the results of the small-group evaluation, it was determined that the course was effective and that students liked the course. The course functions as designed when using the recommended browsers. Data collection from the course tests was successful in Blackboard.